2011
DOI: 10.1080/15389588.2011.561455
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Unhelmeted and Uninsured ATV Drivers and Passengers

Abstract: Helmets are frequently not worn by ATV riders. Helmets protect ATV drivers and passengers and decrease societal costs associated with ATV crashes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…Previous studies have also found that helmet use was even lower in fatal crashes (5–15%),27 again similar to the present results. Passenger helmet use has previously been reported to be lower than operator use in non-fatal crashes,17 28 and we found this was true for fatal crashes as well. Our fatality analysis further demonstrates that helmet use was lower on the roadway than off, among adults as compared with youth, when vehicles had multiple riders, and when alcohol was involved.…”
Section: Discussionsupporting
confidence: 69%
“…Previous studies have also found that helmet use was even lower in fatal crashes (5–15%),27 again similar to the present results. Passenger helmet use has previously been reported to be lower than operator use in non-fatal crashes,17 28 and we found this was true for fatal crashes as well. Our fatality analysis further demonstrates that helmet use was lower on the roadway than off, among adults as compared with youth, when vehicles had multiple riders, and when alcohol was involved.…”
Section: Discussionsupporting
confidence: 69%
“…8,17 Helmets are estimated to reduce the risk of fatal ATV-related head injuries by 40% and of nonfatal head injuries by 60% or more. 8,17,[25][26][27] ATV Crashes Almost 60% of exposed students in our study reported having been in at least 1 crash in their lifetime. This value is similar to the 44% of children at Connecticut agricultural fairs and the 67% of Illinois 4-H club members reporting having crashed.…”
Section: Helmet Usementioning
confidence: 86%
“…A U.S. study using data from the National Trauma Data Bank described helmet use in injured ATV users admitted to hospital between 2000 and 2004. Only 35% of drivers and 19% of passengers were found to be wearing helmets, although information regarding helmet use was missing in a significant proportion of cases [45]. A Canadian study of ATV fatalities similarly found that 37% of ATV riders had been wearing helmets [14].…”
Section: Helmet Usementioning
confidence: 88%